Ocurrence of bla spm-1 and bla imp-1 genes of metallo-B-lactamases in clinical isolates of pseudomonas aeruginosa from three universitary hospitals in the city of Porto Alegre, Brazil - Gaspareto, Patrick Barcelos (2007)
We described the ocurrence of metallo-β-lactamases (MBL) genes blaSPM-1 and blaIMP-1 in clinical isolates of Pseudomonas aeruginosa resistant to imipenem and/or ceftazidime obtained from three universitary hospitals in the city of Porto Alegre, Brazil. The MBL production was screened by phenotypic test and the genes were detected by PCR.